Novel anatomically contoured locking plate shows improved anatomic conformity vs. a conventional T-shaped plate in anterior popliteus transtibial-tuberosity high tibial osteotomy: a radiologic comparison - Yao, Zhonghui; He, Jialin; Chen, Qiuhan; Zou, Zihao; Lei, Da; Wu, Zhanyu; Ye, Chuan (Frontiers in Surgery, 2025)
BackgroundHigh tibial osteotomy (HTO) corrects varus malalignment and unloads the medial knee compartment, yet the conventional T-shaped locking plate may cause discomfort due to suboptimal anatomic conformity. We developed a novel locking plate to improve anatomic fit and fixation stability and compared it with the T-shaped plate in Anterior Popliteus Transtibial-tuberosity high tibial osteotomy (APTT-HTO).MethodsThis retrospective comparative study included 14 consecutive patients who underwent APTT-HTO between August 2024 and June 2025. Patients were grouped by implant type (novel plate: n = 7; T-shaped plate: n = 7). Postoperative CT quantified plate orientation/position, plate–bone conformity (gap and position mismatch), screw alignment, and standard alignment parameters [hip–knee–ankle angle [HKA], posterior tibial slope [PTS]].ResultsThe novel plate showed more posteromedial placement and superior anatomic conformity. The plate angle relative to the posterior tibial condylar reference line was larger with the novel plate (74.49° ± 8.76°) than with the T-shaped plate (62.62° ± 7.05°, P < 0.05). The proximal central screw–plate angle was smaller (5.70° ± 4.80° vs. 27.48° ± 6.05°, P < 0.05), the plate–bone gap was reduced (1.47 (1.35–2.28) vs. 3.12 (2.70–3.26) mm, P < 0.05), and plate position mismatch was lower (18.86 (14.32–23.87) vs. 34.31 (30.57–42.08) %, P < 0.05). Proximal and distal offsets considered separately were not significantly different (P > 0.05). Both groups achieved the planned coronal correction (P < 0.05), and the sagittal PTS remained unchanged (P < 0.05).ConclusionsIn this CT-based cohort, the novel anatomically contoured locking plate achieved superior anatomic conformity in APTT-HTO—characterized by more posteromedial positioning, a more favorable screw trajectory, and improved plate–bone apposition—compared with a conventional T-shaped plate. These findings warrant confirmation in larger, prospective studies.